Pleistocene Chinese cave hyenas and the recent Eurasian history of the spotted hyena, Crocuta crocuta. Issue 3 (9th December 2013) - Sheng, Gui‐Lian; Soubrier, Julien; Liu, Jin‐Yi; Werdelin, Lars; Llamas, Bastien; Thomson, Vicki A.; Tuke, Jonathan; Wu, Lian‐Juan; Hou, Xin‐Dong; Chen, Quan‐Jia; Lai, Xu‐Long; Cooper, Alan
Abstract The living hyena species (spotted, brown, striped and aardwolf) are remnants of a formerly diverse group of more than 80 fossil species, which peaked in diversity in the Late Miocene (about 7–8 Ma). The fossil history indicates an African origin, and morphological and ancient DNA data have confirmed that living spotted hyenas (Crocuta crocuta) of Africa were closely related to extinct Late Pleistocene cave hyenas from Europe and Asia. The current model used to explain the origins of Eurasian cave hyena populations invokes multiple migrations out of Africa between 3.5–0.35 Ma. We used mitochondrial DNA sequences from radiocarbon‐dated Chinese Pleistocene hyena specimens to examine the origin of Asian populations, and temporally calibrate the evolutionary history of spotted hyenas. Our results support a far more recent evolutionary timescale (430–163 kya) and suggest that extinct and living spotted hyena populations originated from a widespread Eurasian population in the Late Pleistocene, which was only subsequently restricted to Africa. We developed statistical tests of the contrasting population models and their fit to the fossil record. Coalescent simulations and Bayes Factor analysis support the new radiocarbon‐calibrated timescale and Eurasian origins model. The new Eurasian biogeographic scenario proposed for the hyena emphasizes the role of the vast steppe grasslands of Eurasia in contrast to models only involving Africa. The new methodology for combining genetic and geological data to test contrasting models of population history will be useful for a wide range of taxa where ancient and historic genetic data are available.